HOTEL HIBURAN DI TEPI PANTAI - Tjahyana, Andrew; Epifania, Priscilla (Jurusan Arsitektur dan Perencanaan, 2019)
Pantai Indah Kapuk area is a residential area that has sufficient carrying capacity. Shopping centers, hospitals, offices, apartments, hotels, education, fitness centers, traditional to modern markets, and entertainment centers such as restaurants and cafes are facilities owned by Pantai Indah Kapuk. With the increasing popularity of the Pantai Indah Kapuk area, the number of visitors to both foreign tourists and local tourists has also increased. Departing from this potential, an entertainment hotel project was designed which is located in Pantai Indah Kapuk 2. With the location of the site that has a border with the sea, it is expected that a hotel facility that emphasizes an activity that has direct contact with nature can have a good impact towards tourists who expect to experience a new experience in entertainment facilities in the capital city of Indonesia. One of the excellent programs of the entertainment hotel facilities is the casino. With the construction of a legal casino facility that can be managed and monitored by the government, it is hoped that a new breakthrough in the tourism sector especially in the capital city of Indonesia can be achieved optimally.